Integrative sperm DNA methylation and miRomics analysis highlights interaction of two epigenetic patterns of pseudomale inheritance in teleost - Zhao, Na; Jia, Lei; Chen, Lu; Lin, Jieyan; Dong, Zhongdian; Zhang, Bo (Frontiers in Marine Science, 2022)
Proper DNA methylation in spermatozoa is essential for the normal development of fertilized embryos through gene expression regulation. Abnormal sperm DNA methylation is associated with male fertility impairment, offspring quality decline, and disease susceptibility. Compared with other epigenetic regulatory mechanisms (e.g., histone modification), DNA methylation is a stable regulator for the long-term transcriptional activity of genes. Sperm DNA methylation is crucial to offspring's survival, development, and reproduction. However, it has not been well studied in teleost to a large extent, especially in some species with sex deviation or congenital sex abnormality in offspring. In the present study, DNA methylation profiles of pseudomale (ZW) and male (ZZ) tongue sole (Cynoglossus semilaevis) spermatozoa were characterized for differential methylation regions (DMRs) screening. The global methylation levels of the two sperm groups were highly methylated with no significant differences. For all kinds of genomic elements, the mean methylation level of the ZW group was higher than that of the ZZ group. The total numbers of Covered C annotated on the W chromosome of both groups were extremely small, suggesting that W-type sperm did not exist in pseudomales. A comparison of methylation levels on 20 sex-related genes between sperm and gonad showed that the heterogeneity between tissue resources was greater than that between sexes, and the methylation level of most genes in gonads was lower than that in sperm. For integrative analysis of DNA methylation and miRomic profiles, 11 sex-related DMRs associated with 15 differentials micro RNAs (miRNAs) in spermatozoa were identified to present targeting relationships and regulatory trends of the two distinct epigenetic patterns. This study provides valuable and potential targets of coordination between two epigenetic mechanisms in the process of C. semilaevis sex congenital bias.